2018
DOI: 10.1103/physrevmaterials.2.053607
|View full text |Cite
|
Sign up to set email alerts
|

Correlated evolution of structure and mechanical loss of a sputtered silica film

Abstract: Energy dissipation in amorphous coatings severely affects high-precision optical and quantum transducers. In order to isolate the source of coating loss, we performed an extensive study of Raman scattering and mechanical loss of a thermally-treated sputtered silica coating. Our results show that loss is correlated with the population of three-membered rings of Si-O4 tetrahedral units, and support the evidence that thermal treatment reduces the density of metastable states separated by a characteristic energy o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 37 publications
6
31
0
Order By: Relevance
“…Indeed, the finding regarding the Urbach tails parallels the well-known (yet still not fully understood) doping-induced reduction of internal friction observed in these films [7]. It has been shown that there is a correlation between mechanical losses and the disordered structure of this coatings [16,25]. The results of this work offer therefore new stimuli for a more systematic investigation of the correlations between the optical properties of high quality Ti-doped tantala coatings, with particular attention to the extension of Urbach tails, and their mechanical properties.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Indeed, the finding regarding the Urbach tails parallels the well-known (yet still not fully understood) doping-induced reduction of internal friction observed in these films [7]. It has been shown that there is a correlation between mechanical losses and the disordered structure of this coatings [16,25]. The results of this work offer therefore new stimuli for a more systematic investigation of the correlations between the optical properties of high quality Ti-doped tantala coatings, with particular attention to the extension of Urbach tails, and their mechanical properties.…”
Section: Resultssupporting
confidence: 74%
“…In this view, a precise determination of refractive index and thickness of coating layers is a key ingredient in the improvement of the mirrors. Adding to this, an accurate knowledge of coating thickness is important in order to evaluate the density of the materials under investigation, which is an essential parameter in the analysis of mechanical loss data providing information about the internal friction [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…In order to represent the complexity of the material, different TLS having a distribution of the ADWP potential V and asymmetry Δ are considered 31 . It is possible to show that at room temperature the internal friction in a material is proportional to the density of TLS that have a barrier height of about 0.5 eV 32 . In fact, following the Arrhenius law, the TLS with lower barrier height are too fast with respect to the period of the external excitation and in this way their contribution to the energy dissipation is negligible.…”
Section: Resultsmentioning
confidence: 99%
“…These changes in the amorphous structure correlate with a reduction of mechanical losses. In another recent work, Raman spectroscopy measurements on SiO 2 coating showed that extended structures such as rings made of three tetrahedrons of SiO 2 (the PSU of SiO 2 ) are correlated to the coating loss angle 32 and have an activation energy of about 0.43 eV 42 . Furthermore, molecular dynamics of AO such as SiO 2 showed that TLS with a barrier of 0.5 eV primarily involves quasi-1D chain of Si-O-Si and rings of Si-O-Si bonds 43 .…”
Section: Discussionmentioning
confidence: 97%
“…In the meanwhile, structural analyses [51][52][53] and molecular dynamics simulations [54-57] might provide critical hints towards a more radical solution of the coating thermal noise issue, to benefit future GW interferometers [28,29].…”
Section: Discussionmentioning
confidence: 99%